Glassy carbon electrode modified with ex-in-situ gold film – A simple and effective working electrode for As(III) determination by using differential pulse anodic stripping voltammetry - Long, Hoang Thai; Le, Thi Kim Dung (Hue University Journal of Science: Natural Science, 2021)
An easy-to-make new working electrode, an ex-in-situ AuF/GCE, was developed for trace As(III) detection. A gold film electrode prepared ex-situ was re-plated in-situ during each arsenic deposition step by adding Au(III) into the analyte solution. The factors affecting arsenic stripping response, namely, gold film preparation conditions, electrolyte concentration, electrode cleaning potential, cleaning time, deposition potential, and deposition time, were investigated. Compared with the traditional gold film electrodes prepared ex-situ, the new electrode has better precision and linearity of arsenic differential pulse anodic stripping voltammetry responses. For a deposition time of 90 s at –200 mV, the new electrode exhibits a sensitivity, a limit of detection (3-Sigma), a limit of quantitation of 0.103 μA·L·μg–1, 0.4 μg·L–1, and 1.3 μg·L–1, respectively.